2014
DOI: 10.1021/jp500408x
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Behavior and Chemical Stability of Silica-Based Nanotubes and Their 3D Assembly

Abstract: Recently discovered amorphous silica-based nanotubes (SBNTs) forming 3D hyperbranched assemblies were studied with transmission electron microscopy. The chemical composition and the element distribution in these template-free synthesized SBNTs were analyzed in depth at the nanoscale with energy-dispersive X-ray and electron energy loss spectroscopy. Furthermore, the bonding behavior of the elements Si, O, N, and P was examined. The SBNTs show a better resistance to extreme pH conditions than pure amorphous sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Independent from the synthesis temperature and SiCl 4 precursor concentration, EDX and EELS analyses reveal that the SBNTs and the hollow particles are predominantly containing Si, O and N, whereas the flakes have a higher amount of P and N. This is in good agreement with our former study of SBNTs synthesized at a temperature of 700 °C and a low SiCl 4 precursor concentration (Dennenwaldt et al, 2014;Sedlmaier et al, 2012). Analyzing the SBNTs synthesized at different temperatures with varying amounts of SiCl 4 precursor, we found that the chemical composition averaged over all reaction products is very similar (Si : O : N : P = 28 : 40 : 25 : 3 at.%), independent from these two parameters.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Independent from the synthesis temperature and SiCl 4 precursor concentration, EDX and EELS analyses reveal that the SBNTs and the hollow particles are predominantly containing Si, O and N, whereas the flakes have a higher amount of P and N. This is in good agreement with our former study of SBNTs synthesized at a temperature of 700 °C and a low SiCl 4 precursor concentration (Dennenwaldt et al, 2014;Sedlmaier et al, 2012). Analyzing the SBNTs synthesized at different temperatures with varying amounts of SiCl 4 precursor, we found that the chemical composition averaged over all reaction products is very similar (Si : O : N : P = 28 : 40 : 25 : 3 at.%), independent from these two parameters.…”
Section: Resultssupporting
confidence: 91%
“…Analyzing the SBNTs synthesized at different temperatures with varying amounts of SiCl 4 precursor, we found that the chemical composition averaged over all reaction products is very similar (Si : O : N : P = 28 : 40 : 25 : 3 at.%), independent from these two parameters. Also, like in previous studies the tip and walls of the SBNTs have the same chemical composition (Dennenwaldt et al, 2014;Sedlmaier et al, 2012). Electron energy-loss near-edge structure (ELNES) analysis of the Si-L 2,3 -edge in the EELS spectra of the samples prepared with a high SiCl 4 precursor concentration reveal that Si is predominantly tetrahedrally coordinated with O and N. The ELNES data of the Si-L 2,3 -edge are in good agreement with those synthesized with a low SiCl 4 precursor content.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations